"Angela's psych squad": Black psychology against the American carceral state in the 1970s. Issue 4 (28th July 2022) - Pettit, Michael
Abstract: This article examines the duality of the Black psychology movement in the United States as both a distinctly American and a postcolonial approach to mental health. The Westside Community Mental Health Center in San Francisco served as the organizational hub for the Association for Black Psychologists (ABPsi) in the 1970s. The Westside clinicians understood forensic psychology as a kind of preventative care as California, more so than any other state, was seduced by the eugenic dream of human improvement through therapeutic interventions in schools and prisons intended to correct the wayward deviant. Their community's mental wellbeing required dismantling the interlinked disciplinary apparatus which disproportionately surveyed, tracked, and confined young Black men. These psychologists mounted a legal challenge to the use of intelligence testing to sort Black children in schools, seeking to replace standardized tests with "dynamic assessments" inspired by Israeli psychologist Reuven Feuerstein's work with refugee children. They consulted on the voir dire process in the highly politicized Angela Davis trial to minimize the presence of racially prejudiced jurors. They offered expert testimony on the psychological damage of solitary confinement on behalf of prison activists. The Westside team artfully developed and deployed the psychological concept of "bias" in their confrontations with local manifestations of the American carceral state. In their theoretical writings, these psychologists reflected upon their historical positionality, understanding themselves as products of the decolonial moment. Bay Area encounters with Third World internationalism, the Black Panther Party (BPP), the Nation of Islam, and community‐led substance abuse programs shaped clinical care at Westside and inspired the Afrocentric consciousness many came to espouse. ABPsi initially had a significant impact on the historically white American Psychological Association's training practices. However, the two organizations split over the IQ controversy at a moment when psychologists became increasingly enmeshed in the criminal justice system